2022
DOI: 10.3390/sym14020414
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Friction Coefficient Calculation in Metal Sheet Forming of Axis-Symmetric Deep Drawing Parts

Abstract: Friction is one of the important factors in sheet metal forming. It greatly affects dynamic behaviors of metal sheets and stress and strain distributions in the metal sheets. In this study, deformation characteristics, stress–strain distribution, and change law of symmetrical parts in the process of deep drawing are analyzed using a new theoretical model based on the plastic flow law and partitioning the forming area. In the model, the least-square method is used to linearize the friction coefficient in nonlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Lubricants 2024, 12, x FOR PEER REVIEW 3 of 14 relevant determination approach for the prediction of the technological characteristics of the deep drawing process [39,40]. The aim of this paper is to study the tribological and corrosion properties of a thin organic coating (TOC) based on hydroxyl resins dissolved in water and compare them with a standard Zn coating and a passivated one.…”
Section: Experimental Materials-substrate and Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lubricants 2024, 12, x FOR PEER REVIEW 3 of 14 relevant determination approach for the prediction of the technological characteristics of the deep drawing process [39,40]. The aim of this paper is to study the tribological and corrosion properties of a thin organic coating (TOC) based on hydroxyl resins dissolved in water and compare them with a standard Zn coating and a passivated one.…”
Section: Experimental Materials-substrate and Coatingsmentioning
confidence: 99%
“…To determine the lubrication properties (the value of the friction coefficient on the contact surfaces of the die and the blank holder), the well-known formability test-the cup test-was used, which simulates the stresses on the material in a real deep drawing process [38][39][40]. This test can be used to describe the most frequent contacts in the tribological system between the tool (punch, blank holder, die), friction material (sheet metal specimen/product) and intermediate material (lubricant, oil, foil or permanent special coating on sheet metal)-Figure 3 [12,38].…”
Section: Cup Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Research projects on the influence of parameters such as blocking force and die geometry on the quality of stamping products, such as limiting earing height, wrinkling, and tearing [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16]. Research on the effects of friction to improve drawing efficiency has been published [17], [18], [19], [20], [21], [22], [23], [24], [25]. The influence of material parameters on the quality of stamping products has been reported [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the solution coincides with an available relation if the friction factor is small enough. Meanwhile, the Coulomb friction law is often used for describing metal forming processes [Dubar et al, 9 Hwang and Chen, 10 Xia et al, 11 Schmidt et al, 12 and Bo¨hnke et al, 13 among many others]. Therefore, applying the theorem 7 to various metal forming processes is necessary.…”
Section: Introductionmentioning
confidence: 99%